A NOVEL ANALYSIS ON LIGHT ESCAPING FROM BLACK HOLE - Kaliyannan, Raja; S, Karthick.; .K, Raja; K, Yadhari.; S, Kalpanadevi; Vanitha.N, Suthanthira (Innovare Journal of Engineering and Technology, 2014)
Abstract: Science must be fact. All the black hole theories said that the light can't escape from the black hole; it will be bent by either gravity or curved space, but this paper proves that the light does not affected by any gravity. It does not falsify black hole theories as a whole. The intent is to fortify space science. It brings some empirical evidence to prove the intention. The escape velocity concept is not applicable for light. The general theory of relativity has no valid basis in science. The only evidence Eddington's experiment also proved by this article as in valid.Â Black hole may exits but light bending, absorption concepts have no possibilities.Â This paper also presents a novel reason for bending light. The light bending happens near the stars only by refraction in the atmosphere of the stars like refraction of light in water, not by the gravity. This paper fully supports newton's theory of gravity. Â Keywords: Â Escape velocity, light bending, Black hole, General relativity, Refraction in star.